2020
DOI: 10.1007/s40201-020-00542-4
|View full text |Cite
|
Sign up to set email alerts
|

Ambient air particulate matter (PM10) satellite monitoring and respiratory health effects assessment

Abstract: Purpose Air particulate matter with an aerodynamic diameter of 10 µm or less (PM 10 ) is one of the main causes of acute exacerbation of chronic obstructive pulmonary disease (AECOPD). This study explored the relationship between PM 10 by remote sensing and AECOPD in Chaharmahal-o-Bakhtiari province from 2014 to2018. Method PM 10 concentrations were predicted and validated based on aerosol optical depth (AOD) from 161 images processed by MODIS sensor and ground air quality monitoring station data. Demographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Although prior studies have reported on the association between air pollution and COPD admissions (Boehm et al., 2021 ; Chen et al., 2020 ; Du et al., 2021 ; Mohebbichamkhorami et al., 2020 ; Sun et al., 2018 , 2019 ), little is known about the effects of CO on the admissions of COPD comorbidities. A study conducted in Qingdao, China, on the association between air pollution and COPD showed no association between CO and COPD (Yang et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although prior studies have reported on the association between air pollution and COPD admissions (Boehm et al., 2021 ; Chen et al., 2020 ; Du et al., 2021 ; Mohebbichamkhorami et al., 2020 ; Sun et al., 2018 , 2019 ), little is known about the effects of CO on the admissions of COPD comorbidities. A study conducted in Qingdao, China, on the association between air pollution and COPD showed no association between CO and COPD (Yang et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although prior studies have reported on the association between air pollution and COPD admissions (Boehm et al, 2021;Chen et al, 2020;Du et al, 2021;Mohebbichamkhorami et al, 2020;Sun et al, 2018Sun et al, , 2019, little Note. Overall cumulative effects of six pollutants lasting for 0-3 days (lag03) were estimated after controlling for public holidays, DOW, cubic spline variables (calendar day for time trends and seasonality.…”
Section: Discussionmentioning
confidence: 99%